1993
DOI: 10.1111/j.1365-3040.1993.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a long‐term water stress on the metabolism and emission of terpenes of the foliage of Cupressus sempervirens

Abstract: The effects of long‐term water stress on water and terpene contents of the foliage of Cupressus sempervirens were studied. A great deal of water was lost over 2 months before a remarkable stabilization. A strong decrease of all the classes of terpenes accompanied this dehydration. Mono‐ and sesquiterpene hydrocarbons and free terpenols were almost entirely metabolized, whereas esters and terpene glycosides rose slightly and remained at a constant level when the water content had stabilized. Although a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…The compounds detected also were similar to those in the previous two studies, but the monoterpene proportions were similar only to those in Yani et al (1993). Yatagai et al (1995) reported that limonene was responsible for 83 % of the emission blend, however, limonene represented only ca.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The compounds detected also were similar to those in the previous two studies, but the monoterpene proportions were similar only to those in Yani et al (1993). Yatagai et al (1995) reported that limonene was responsible for 83 % of the emission blend, however, limonene represented only ca.…”
Section: Discussionsupporting
confidence: 85%
“…Foliar Emission Rates Foliar terpene emission rates of the control ranged between 2 and 4 μg g −1 dw h −1 , similar to rates reported by Yatagai et al (1995) and Yani et al (1993) for the same species. The compounds detected also were similar to those in the previous two studies, but the monoterpene proportions were similar only to those in Yani et al (1993).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…2), applied over a finite C i range of ca. 150-330 µmol mol −1 , isoprene emission is relatively insensitive over this range or moderately increases at lower C i , likely explaining the insensitivity of isoprenoid emissions to mild stress Peñuelas et al, 2009;Sharkey and Loreto, 1993;Staudt et al, 2002), or the moderately increased emissions occasionally observed under mild stress (Bertin and Staudt, 1996;Pegoraro et al, 2005;Staudt et al, 2008;Yani et al, 1993).…”
Section: Influence Of Droughtmentioning
confidence: 96%
“…Neryl acetone (Helmig et al, 2006), terpinyl acetate (Yani et al, 1993) and nonenal (Helmig et al, 1999) have also been observed using enclosure measurement techniques.…”
Section: Model Parametersmentioning
confidence: 99%